TISCs and TTOs report 2022 : strengthening local innovation capacities to accelerate knowledge and technology transfer. (WIPO, World Intellectual Property Organization, 2022)
This annual report for Technology and Innovation Support Centers (TISCs) and Technology Transfer Offices (TTOs) highlights the main developments and milestones in 2022, with a focus on how TISCs in 90 countries and TTOs continued to expand their services to meet the needs of local innovators, and how WIPO supports them with new resources.
Keywords: Technology and Innovation Support Centers.; Technology Transfer Offices.; Technological innovations.; Intellectual property.; Innovations.; Propriété intellectuelle.; intellectual property.; Electronic books.